A perspective on anti-inflammatory properties of Cleome gynandra - Mohamad Rosdi , M.N.; Awang, M.A; Abu Bakar, M.H. (Rynnye Lyan Resources, 2024)
Cleome gynandra L. is a widely consumed leafy vegetable. This plant is grown as a weed and widely distributed in tropical and subtropical regions such as Africa, South Asia, and Southeast Asia. In Malaysia, this plant is known as 'maman' and is commonly consumed in stew and pickles. Cleome gynandra contains various natural bioactive including flavonol, glycoside, flavonoids, essential oils, bicyclic diterpenes, triterpenoids, coumarinolignoids and dipyridodiazepinone substances that have nutritional values and health-promoting characteristics. Numerous investigations have shown this plant exhibited significant pharmacological activities, including antioxidant, anticancer, anti-arthritic, antiparasitic, antimalarial, antifungal, and anti-inflammatory. Various reports showed that the C. gynandra extracts significantly reduced paw edema in adjuvant arthritis-induced rats. Nonetheless, a comprehensive review investigating the anti-inflammatory attributes of this plant has not yet been conducted. This paper aimed to explore the antiinflammatory activities of C. gynandra and its potential mechanism of action.